Is Food Addictive? A Review of the Science - Gearhardt, Ashley N; Schulte, Erica M (Annual review of nutrition, 2021)
As ultraprocessed foods (i.e., foods composed of mostly cheap industrial sources of dietary energy and nutrients plus additives) have become more abundant in our food supply, rates of obesity and diet-related disease have increased simultaneously. Food addiction has emerged as a phenotype of significant empirical interest within the past decade, conceptualized most commonly as a substance-based addiction to ultraprocessed foods. We detail ( ) how approaches used to understand substance-use disorders may be applicable for operationalizing food addiction, ( ) evidence for the reinforcing potential of ingredients in ultraprocessed foods that may drive compulsive consumptions, ( ) the utility of conceptualizing food addiction as a substance-use disorder versus a behavioral addiction, and ( ) clinical and policy implications that may follow if ultraprocessed foods exhibit an addictive potential. Broadly, the existing literature suggests biological and behavioral parallels between food addiction and substance addictions, with ultraprocessed foods high in both added fat and refined carbohydrates being most implicated in addictive-like eating. Future research priorities are also discussed, including the need for longitudinal studies and the potential negative impact of addictive ultraprocessed foods on children.